An empirical analysis of impact of bonus issue on share price with reference to selected companies in india - S, POORNIMA; V, CHITRA (Journal of Management and Science, 2012)
This study examines the impact of bonus issue on share price of selected scrip’s during February 2010 to February 2011 listed on National Stock Exchange, India. When additional shares are allotted to existing shareholders without being paid any additional payment for them, it is known as bonus shares. Bonus shares are issued by a company when it intends to pay dividend by issuing shares. Companies giving bonus shares are regarded very highly by investor fraternity. Very few studies have observed bonus issue announcement and share prices in India and this study is an attempt to fill the gap. The present study is an empirical analysis to examine the impact of bonus announcement on share prices. Impact has been analyzed between 7 days from the date of bonus announcement. The result divulges that there is no significant impact on bonus announcement between pre-post conditions considered for this study.